Carbon–nitrogen–metal material as a high performing oxygen evolution catalyst. Issue 10 (11th May 2022) - Fruehwald, Holly M.; Zenkina, Olena V.; Easton, E. Bradley
Abstract : Oxygen evolution reaction catalysts composed of Ni–N3 molecular motifs grafted onto carbon black. Abstract : Novel oxygen evolution catalysts were prepared through diazonium coupling chemistry to covalently modify Vulcan carbon via terpyridine (tpy) motifs followed by coordination of non-precious transition metals (Ni, Co) to the tpy-ligand on the surface support. This resulted in highly active catalysts that demonstrate low overpotentials for the V-tpy-Ni catalyst of 313 mV at 10 mA cm −2, and stable long-term performance over 26 hours of continual testing.